When digitalization meets omnichannel in international markets: A case study from the agri-food industry - Maria Vincenza Ciasullo; Raffaella Montera; Francesco Mercuri; Shame Mugova (Administrative Sciences, 2022)
Digitalization is prompting small and medium-sized enterprises to structural and strategic transformations, also providing new opportunities to expand and succeed in foreign markets. However, relatively few studies have investigated emergent digital technologies in international business management. Contextually, there is still a dearth of research on the multi-faceted impacts of digitalization on omnichannel strategy characterizing most of the global business environment today. This paper, therefore, aims to examine the impact of digitalization on omnichannel choices adopted by internationalized SMEs. A qualitative approach, based on a single case study methodology, is adopted. An Italian agri-food SME is chosen as this industry is considered a key and distinctive pillar of Made in Italy in the international markets. Findings reveal the potential of digital technologies' applications in an omnichannel environment, blurring the boundaries between channels, through a synergetic integration of them. This evidence contributes to the existing literature on technology management and omnichannel strategies in the international context by rereading these phenomena through a smart ecosystem lens. In addition, this study provides practical insights on how multiple channels adopted by Made in Italy SMEs can be integrated, managed, and operated synergistically on international markets to sustain a digitalized value creation.
Keywords: 350; agri-food; digitalization; internationalization; Made in Italy SMEs; omnichannel